Managers' Resources for Authentic Leadership – a Multi-study Exploration of Positive Psychological Capacities and Ethical Organizational Climates - Martin P. Fladerer; Susanne Braun (British Journal of Management, 2020)
While authentic leadership is highly valued in today's business world, managers do not necessarily have the resources to attain it. Building on conservation of resources theory, we propose a conceptual model to address how personal and contextual resources predict authentic leadership. Study 1 analyses the day-to-day variability in managers' positive psychological capacities as personal resources in relation to changes in authentic leadership. In addition, it tests ethical organizational climates as stable, contextual resources for authentic leadership. In Study 2, we replicate our results on the between-person level and extend the research model by exploring promotion focus as a link in the relationship between personal resources and authentic leadership. Evidence from an experience sampling study with 89 managers surveyed daily on 10 consecutive working days (Study 1) and a field survey of 130 managers at two points in time (Study 2) supports the hypothesized role of personal resources and promotion focus for authentic leadership. In both studies, only principled but not benevolent ethical organizational climates emerged as a contextual resource for authentic leadership. We discuss the implications for current management research and practice.
Keywords: 650